Cost objects: How is your ED performing? - Verónica Fuentes-Cáceres; Liliana Neriz; Alicia Núñez-Mondaca; Ricardo Mateo (BMC, 2020)
Abstract Background The aim of this study is to a propose a standardized methodology to identify a list of cost objects that can be used by any ED to compute costs considering that the resulting data must facilitate unit management by improving the information available for decision-making. Methods This study considers two stages, first, we analyzed the case-mix of two hospitals collecting their data to define and diagram their processes, activities and to obtain their cost objects, second, we used four additional hospitals to validate our initial findings. Results We recognized 59 cost objects. Hospitals may have all these cost objects or just a subset of them depending on the services they provide. Conclusions Among the main benefits of our cost objects definition are: the possibility of tracing the processes generated by the services delivered by EDs, the economic sense in its grouping, the chance of using any costing methodology, the flexibility with other classification systems such as DRGs and ICDs, and the opportunity of costing for both diseases and treatments. Furthermore, cost comparison among hospitals using our final 59 cost objects list is more accurate and based on comparable units. In different EDs, each cost object will be the result of a similar combination of activities performed. We also present the results of applying this cost objects list to a particular ED. A total of 53 out of 59 cost objects were identified for that particular unit within a calendar year.